2002
DOI: 10.1126/science.296.5569.873
|View full text |Cite
|
Sign up to set email alerts
|

Female Eavesdropping on Male Song Contests in Songbirds

Abstract: Male song reflects the quality of the singe many animals and plays a role in female ch, of social and copulation partners. Eavesdropi on male-male vocal interactions is a means which females can compare different ma singing behavior directly and make immed comparisons between potential partners the basis of their relative vocal performa (1, 2). Using an interactive playback exp ment followed by microsatellite pater analysis, we investigated whether female black-capped chickadees (Poecile atricapilla) base thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
207
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(216 citation statements)
references
References 4 publications
8
207
1
Order By: Relevance
“…The biological significance of variation in song has not been studied in house sparrows but the acoustic structure of song may encode information important to both sexes such as individual identity, dominance status, parasite load, fighting and parenting abilities and genetic quality, as in other songbirds (Collins, 2004). Females may use this information to choose social mates or partners for extra-pair copulations, as shown in blackcapped chickadees [Poecile atricapillus (Mennill et al, 2002)]. In house sparrows, 40% of males in an Oklahoma population were found to be cuckolded, and 20% of offspring could be attributed to extrapair fertilizations (Whitekiller et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The biological significance of variation in song has not been studied in house sparrows but the acoustic structure of song may encode information important to both sexes such as individual identity, dominance status, parasite load, fighting and parenting abilities and genetic quality, as in other songbirds (Collins, 2004). Females may use this information to choose social mates or partners for extra-pair copulations, as shown in blackcapped chickadees [Poecile atricapillus (Mennill et al, 2002)]. In house sparrows, 40% of males in an Oklahoma population were found to be cuckolded, and 20% of offspring could be attributed to extrapair fertilizations (Whitekiller et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in female black-capped chickadees, Poecile atricapillus, the probability of extra-pair copulations depends on the outcome of male-male vocal contests. By experimentally manipulating the outcome of contests between the female's social partner and either an aggressive or submissive simulated opponent, Mennill et al (2002Mennill et al ( , 2003 showed that females paired with high-ranking males were more likely to accept extra-pair sires when their partner had been exposed to aggressive rather than to submissive opponents. Interestingly, Ophir and Galef (2004) showed that, in Japanese quails, the use of public information depends on females' previous sexual experience: when observing an antagonistic interaction between two males, young virgin females preferred the most aggressive male, whereas the sexual experienced females preferred the least aggressive male.…”
Section: S Castellano Et Al / Behavioural Processes XXX (2012) Xxx-xxxmentioning
confidence: 99%
“…Furthermore, observations of singing in songbird neighborhoods reveal that the interactive communication is usually an ongoing process that lasts throughout the breeding season, and that birds may use direct interaction as well as eavesdropping on other interactions to continually adjust their assessment of the status of their neighbors. For example, recent field experiments on songbirds have shown that males make decisions concerning whom to challenge and females make decisions concerning whom to mate with based on information acquired by eavesdropping on singing interactions (Naguib & Todt, 1997;Otter et al, 1999;Mennill et al, 2002). In the species studied to date, song overlapping, song-type matching, frequency matching, and/or song leading seem to be some of the critical cues that indicate relative status between two singers (Mennill & Ratcliffe, 2004;Peake et al, 2005;Kunc et al, 2006).…”
mentioning
confidence: 99%